The trickster shadow - Pawis-Steckley, Joshua Mangeshig (Little, Brown and Company, a division of Hachette Book Group, Inc., 2025)
"Drawing on Indigenous ancestral wisdom and inner strength, a child is able to master the dark side of his emotions"--